High step‐up DC–DC converter composed of quadratic boost converter and switched capacitor. Issue 17 (22nd January 2021) - Rezaie, Milad; Abbasi, Vahid; Kerekes, Tamas
Abstract : This study proposes a high step‐up DC–DC converter which is composed of a conventional quadratic boost converter, a switched capacitor and a coupled inductor. To reduce the number of components, the primary side of the coupled inductor is shared with the quadratic boost converter as one of its inductors. Furthermore, the output capacitor of the quadratic boost converter is divided into two capacitors and one of them is utilised in common with the switched capacitor. The converter is analysed and the obtained equations are used to compare the proposed converter with other converters which have similar structures. According to the comparisons, the proposed converter has advantages such as higher voltage gain, the lower voltage stress on the power switch and requiring a smaller inductor. In addition, the input source current is continuous and there is a common ground between the source and load. Increasing the turn ratio of the coupled inductor causes reduction of voltage stress on the power switch, diodes and capacitors. To investigate performance of the proposed converter, an 80 W prototype is built. The experiments show good accordance with the analysis and they demonstrate the high step‐up capability of the proposed converter.